Focal hemisphere and visuoperceptual categorization. Issue 11 (November 1975) - Bisiach, E; Capitani, E; Spinnler, H
Abstract : Visuoperceptual categorization was investigated in patients with unilateral brain damage by a task in which meaningless shapes had to be classified with reference to a number of prototype patterns. Right brain-damaged subjects with visual field defect turned out to have a narrower categorization span. As this outcome seems to be scarcely consonant with a lower level disorder of visual processing, a major competence of the right hemisphere is suggested for visuoperceptual categorization.